Effect of different treatment of sugarcane fiber on mechanical properties, morphology and swelling behavior of low density polyethylene (LDPE) composites - Zamzarina Hasim
The sugarcane bagasse is a residue widely generated in high proportions in the agroindustry. In this research, the bagasse fiber has been used as reinforcing component for polyethylene. The chemical treatments using sodium hydroxide (NaOH) and maleic acid (MA) were carried out to modify the fiber properties. The effects of different chemical contents on the composites were investigated.